Damping of magnetospheric toroidal Alfvén eigenmodes due to phase mixing - Cheremnykh, S.O.; Parnowski, A.S. (Advances in Astronomy and Space Physics, 2013)
We demonstrate that toroidal shear Alfvén eigenmodes in dipolar magnetostatic plasma equilibrium are subject to damping due to phase mixing. This result is of particular interest for the investigation of Pc5-6 geomagnetic pulsations.